2021
DOI: 10.1007/s43681-021-00104-w
|View full text |Cite
|
Sign up to set email alerts
|

Identifying key ethical debates for autonomous robots in agri-food: a research agenda

Abstract: Agribusinesses are investing in different forms of AI robots, as there is a lot of hope that these machines will help meet the challenges within the agricultural industry, which is to efficiently produce more food for a growing world population. AI robots are expected to enhance production, while compensating for lack of manpower, reducing production costs, taking over unattractive (risky, heavy, and dirty) jobs and reducing the burden of food production on the environment. In spite of these promises, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 70 publications
(90 reference statements)
1
21
0
Order By: Relevance
“…There has been limited work focused on the anticipation of farm system-level implications of robotics and automation in agriculture (Legun and Burch, 2021;Rose et al, 2021b;Ryan et al, 2021). We propose that part of the anticipatory process is to lead innovation through design with a systems-thinking lens (Romera et al, 2020;Eastwood et al, 2022).…”
Section: Responsible Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been limited work focused on the anticipation of farm system-level implications of robotics and automation in agriculture (Legun and Burch, 2021;Rose et al, 2021b;Ryan et al, 2021). We propose that part of the anticipatory process is to lead innovation through design with a systems-thinking lens (Romera et al, 2020;Eastwood et al, 2022).…”
Section: Responsible Innovationmentioning
confidence: 99%
“…A review by Ingram et al (2022) identified priority research questions in agriculture, including the need to understand factors influencing the uptake of digital technology, how to include farmer perspectives in design of digital tools, and anticipating potential effects of such technologies on agriculture and agricultural work. Ryan et al (2021) note research themes around benefit distribution of robots in agriculture, potential impacts on the idea of the "good farmer", how robots can contribute to positive animal welfare, and the duality of enacting sustainable farming with robots. The interaction between robots and work have been explored in several studies (Legun and Burch, 2021;Nazareno and Schiff, 2021;Rose et al, 2021a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The former type of AI involves retrieving an abundance of data from the farm, local climate, data from machinery, and so forth, and integration AI methods (machine learning, deep learning, and reinforcement learning) to forecast and prescribe recommendations for the farmer about when to seed, harvest, and sell their crops; the health and behaviour patterns of their livestock; and image recognition to detect plant disease (to list only a few examples). Whereas, AI robots work (relatively) autonomously on the farm to harvest fruit and vegetables (such as peppers in the SWEEPER project), garden, scrape manure (LELY Robot), weeding robots (the Weed Wacker robot), drones to spray weeds and pesticides (ecorobotix), and robots that hoe and harvest (NAIO technologies' robots), and to measure crop health (agribotix) (examples taken from (Ryan et al 2021). 1 This paper will examine published articles and conference proceedings that focus on societal or ethical impacts of AI in the agri-food sector, through a thematic analysis of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of AI-based agricultural tools include machines that are used on farms to hoe and harvest crops, perform weeding, drones to spray weeds and pesticides (Ryan et al, 2021b), and devices used in automatic milking (Shamshiriet et al, 2018). Robots have contributed to reducing the volume of chemicals sprayed on the crops by 80% (Revanth, 2019).…”
Section: Introductionmentioning
confidence: 99%